An Intellectual and a Peasant in Gleb Uspensky’s Cycle “Peasant and Peasant Labor”: Dynamics of Interaction in Context of Idea of “Merging with People” - T. V. Dyachuk (Научный диалог)
The cycle of essays by G. I. Uspensky “The Peasant and the Peasant Labor” in the aspect of the actual for Russian literature of the second half of the XIX — early XX centuries problems of relations between the people and the intellectuals are analyzed in the article. The crisis in the study of the “peasant” cycles of Uspensky, caused by the predominance of ideological interpretation, is stated. It is argued that Uspensky finds the key to understanding the peasantry not in the socio-economic conditions of his life, but in the field of aesthetics. The point of convergence, in which the peasant and the intellectual appear as equal subjects of communication, is, according to Uspensky, the aesthetic attitude to work. An implicit correspondence is established between peasant labor and the creative effort of the artist. Therefore, the intellectual turns out to be a necessary mediator in the process of the peasantry acquiring its own “voice”. It is proved that the aesthetic utopia in the cycle “Peasant and Peasant Labor” was crushed by the ethical maximalism of the writer. The peasant economy is represented by the Uspensky reasonably organized order, the anthroposphere, in which the working peasant was likened to the monarch and the Creator. In turn, the intellectual was declared an impostor, marked by the “antichrist” seal. In Uspensky’s creative consciousness, the aesthetic and ethical found themselves in a tragic and hopeless contradiction, and the prospect of “merging with the people” was illusory.